Implemetasi Jaringan Saraf Tiruan Untuk Mendeteksi Serangan DDoS Pada Forensik Jaringan - Muhammad Aziz; Rusydi Umar; Faizin Ridho (Program Studi Sistem Informasi, 2019)
Network attacks that are often carried out including using Distributed Denial of Service (DDoS) have caused significant financial losses and require very large recovery costs to reach double. Activities that damage, interfere with, steal data, and anything that harms the system owner of a computer network is illegal and can be legally sanctioned in court. Network forensics mechanism to find criminals in order to be ensnared by law. Investigators usually use network monitoring systems such as Intrusion Detection System (IDS) for forensics purposes. The use of IDS allows the detection of errors or changes in traffic and new types of attacks because attacks are carried out using syn packages, where the syn protocol is considered legal because it is needed in the authentication process of communication between devices in the Internet network. Signature-based detection and notification systems are also not strong enough to be used as evidence in the trial. An analysis mechanism is needed to test the accuracy of DDoS attacks that have been detected by the intrusion detection system. Testing the accuracy of DDoS attacks can be done using the neural network classification method using statistical calculations. Based on the results of the analysis and testing carried out found an accuracy value of 95.23%. These results can be used to support and strengthen the evidence of findings in the trial.Keywords: DDoS, IDS, network forensics, JST